Roadblocks on the road to grandma's house: Fertility consequences of delayed retirement - Erich Battistin; Michele De Nadai; Mario Padula (Queen Mary University of London, School of Economics and Finance, 2015)
We investigate the role of grandparental childcare for fertility decisions of their offspring. Exploiting pension reforms in Italy, we argue that delayed retirement represents a negative shock to the supply of informal childcare for the next generation. We show that, when the maternal grandmother is not available, motherhood after age 30 is less likely. This effect persists as the woman ages, and parallels that on number of children. We argue that these are permanent changes to completed fertility for many cohorts in our data. Consistent with our interpretation, we show that results are limited to the most familistic close-knits where the role of grandparents is more important, and that are not the mechanical consequence of changes of living arrangements and labor supply. Given the Italian lowest low fertility, we conclude that pension reforms may have had unintended inter-generational effects.
Keywords: J08; J13; H42; 330; Fertility; Informal child care; Pension reforms